Performance, Nutrient Digestibility, and Meat Quality of Bali Cattle Fed a Ration Supplemented with Soybean Oil Calcium Soap and Cashew Fruit Flour - A. Bain; D. A. Astuti; S. Suharti; C. Arman; K. G. Wiryawan (Faculty of Animal Science, Bogor Agricultural University, 2016)
The study to evaluate growth performance, nutrient digestibility, blood metabolites profile and meat fatty acid of Bali cattle treated with 3 different types of rations were conducted using a completely randomized block design with 4 replications. Ration treatments were R1: 40% native grass (NG) + 60% concentrate, R2: 40% NG + 60% concentrate supplemented with 5% soybean oil calcium soap (SOCS), and R3: (40% NG + 60% concentrate supplemented with 5% SOCS + 10% cashew fruit flour (CFF). Variables measured were growth performance, nutrients digestibility, blood metabolites, and meat fatty acid profile. Data were analyzed using analysis of variance (ANOVA) and the differences between treatment means were examined by Duncan Multiple Range Test. Results of the study showed that the 3 different feed treatments did not have any significant effect on dry matter intake and organic matter intake, daily body weight gain, feed efficiency, crude fiber, ADF and NDF digestibilities, cholesterol, triglycerides, low density lipoprotein (LDL), high density lipoprotein (HDL), total fatty acid contents and content of unsaturated and saturated meat fatty acids of Bali cattle meat. Different treatment rations also did not affect dry matter digestibility, however the treatments significantly affect the organic matter, crude protein, and fat digestibility (P<0.05). Bali cattle fed 5% SOCS (R2) and 5% SOCS + 10% CFF (R3) had higher organic matter and ether extract digestibilities and linoleic acid content of meat (P<0.05) compared with the control (R1). The Bali cattle fed with R1 and R2 had higher crude protein digestibility (P<0.05) compared with that of R3. It is concluded that the supplementation of 5% SOCS and 10% CFF in the ration improved the digestibility of organic matter, ether extract and linoleic fatty acids content in Bali cattle meat.